Experimental study for thermal methane cracking reaction to generate very pure hydrogen in small or medium scales by using regenerative reactor - Yousefi, Mahdi; Donne, Scott (Frontiers in Energy Research, 2022)
Non-catalytic thermal methane cracking (TMC) is an alternative for hydrogen manufacturing and traditional commercial processes in small-scale hydrogen generation. Supplying the high-level temperatures (850–1800°C) inside the reactors and reactor blockages are two fundamental challenges for developing this technology on an industrial scale (Mahdi Yousefi and Donne, 2021). A regenerative reactor could be a part of a solution to overcome these obstacles. This study conducted an experimental study in a regenerative reactor environment between 850 and 1,170°C to collect the conversion data and investigate the reactor efficiency for TMC processes. The results revealed that the storage medium was a bed for carbon deposition and successfully supplied the reaction’s heat, with more than 99.7% hydrogen yield (at more than 1,150°C). Results also indicated that the reaction rate at the beginning of the reactor is much higher, and the temperature dependence in the early stages of the reaction is considerably higher. However, after reaching a particular concentration of Hydrogen at each temperature, the influence of temperature on the reaction rate decreases and is almost constant. The type of produced carbon in the storage medium and its auto-catalytic effect on the reactions were also investigated. Results showed that carbon black had been mostly formed but in different sizes from 100 to 2000 nm. Increasing the reactor temperature decreased the size of the generated carbon. Pre-produced carbon in the reactor did not affect the production rate and is almost negligible at more than 850°C.